Protein supplementation in pediatric oncology: a systematic review revealing a lack of evidence and insights from other chronically and critically ill children - den Hartog, Emma; van Tongeren, José; van Dalen, Elvira C.; van den Brink, Mirjam; Verwaaijen, Emma J.; Tissing, Wim J. E. (Frontiers in Pediatrics, 2025)
Background & aimsExercise interventions may counteract adverse effects of childhood cancer (treatment) on anthropometrics, body composition and physical fitness. However, inadequate nutritional status and loss of muscle mass and strength might limit effectiveness. Protein supplementation might support muscle preservation and enhance the benefits of exercise but evidence on its effect in children with cancer is lacking. This review examined the potential effect of protein supplementation on anthropometrics, body composition, physical fitness and adverse effects in children with cancer from diagnosis until two years after end of treatment.MethodsPubMed/MEDLINE was searched for literature on childhood cancer and protein supplementation (14th of May 2025). Reports examining anthropometrics, body composition and/or physical fitness before and after the protein intervention and written in English were eligible. Another search was performed in chronically and critically ill children (14th of May 2025). Risk of bias was assessed using Cochrane Childhood Cancer criteria and for each outcome, we graded the quality of evidence using the Grading of Recommendations Assessment, Development and Evaluation methodology. Data were descriptively reported.ResultsNone of the studies in children with cancer could be included. Five studies were included with a total of 142 children (66 had cystic fibrosis, 6 Crohn's disease, 70 a prolonged pediatric intensive care unit stay). Protein supplementation interventions varied. All studies reported on anthropometrics and body composition. Four observational studies reported a significant improvement in at least one of the outcomes whereas one randomized controlled trial (RCT) found no significant changes. Of the three studies assessing physical fitness measurements, two observational studies reported a significant improvement in at least one of the outcomes while one RCT did not find a significant change. The three studies reporting on adverse effects were encouraging but this outcome deserves further investigation. Level of evidence was graded very low for all outcomes.ConclusionsEvidence on the potential of protein supplementation is scarce and not available in children with cancer. The limited evidence included in this review tentatively suggests that protein supplementation might aid in improving anthropometrics, body composition and physical fitness. Future controlled trials are needed to determine its feasibility and effectiveness in children with cancer.